Karsinoma Nasofaring: Sebuah Laporan Kasus - Gatra Hadimuti Wibowo; Ratu Fajaria; Risti Graharti (CV. Jasa Sukses Abadi, 2026)
Nasopharyngeal carcinoma (NPC) is a malignant tumor originating from the nasopharyngeal epithelium and is the fourth most common malignancy in Indonesia, with approximately 13,000 new cases annually. Diagnosis is often delayed due to the concealed location of the nasopharynx. Case presentation: A 40-year-old male presented with left-sided tinnitus, earache radiating to the head, hearing loss, nasal congestion, odynophagia, hoarseness, and a 5-7 kg weight loss over 4 months. He had a history of Bell's palsy 8 months prior with House-Brackmann grade III that partially improved. Physical examination revealed no cervical lymphadenopathy. Nasopharyngeal CT scan showed left nasopharyngeal thickening, narrowing of the Rosenmüller fossa, and a hypodense lesion in the left temporal lobe suggestive of intracranial invasion. Discussion: This case is unique due to the combination of early manifestation as Bell's palsy without cervical lymphadenopathy, which differs from the typical NPC pattern where 70-90% of patients present with cervical metastases. Facial nerve involvement in NPC is rare (incidence <1%) and often overlooked as an early sign of malignancy. MSCT and MRI imaging play a crucial role in early detection of intracranial invasion. Conclusion: NPC should be suspected in adults with persistent ear, nose, and throat symptoms accompanied by weight loss, especially if there is an atypical history of Bell's palsy, even in the absence of cervical lymphadenopathy. Histopathological confirmation through nasopharyngeal biopsy remains essential before definitive management.